Impact of fertilizer doses on growth and grain yield under different rice cultivation methods - Shaik Mohammad Rafi; Amod Kumar Thakur; Om Prakash Verma; Rajkumari Bhol; Kaushik Kumar Panigrahi; Prabhasmita Shatpathy (Annals of Agricultural Research, 2024)
A field experiment was conducted at ICAR-Indian Institute of Water Management Research Farm, Mendhasal, Odisha, during the Rabi season of 2024 to study the effect of different crop management practices in rice with varying NPK doses on growth, yield attributes and grain yield. The experiment was laid out in a factorial split-plot design with three replications, comprised of two crop establishment methods of rice, viz.system of rice intensification (SRI) and conventional transplanting system (CTS) in the main plot and the sub-plot treatments were 0% of the recommended dose of fertilizer (RDF), 25% of RDF, 50% of RDF, 75% of RDF, 100% of RDF, 125% of RDF. The recommended dose of fertilizers was 80 kg N, 40 kg P2O5, and 40 kg K2O ha-1. It was found that the highest grain yield for both SRI (5.89 t ha-1) and CTS (4.56 t ha-1) was observed in T5-100% RDF, and overall, SRI produced 30% higher grain yield than CTS. This higher grain yield under SRI was due to significant improvements in the number of panicles m-2 (by 15%), grains number panicle-1 (by 26%), grain filling % (by 11%), and 1000-grain weight (by 6%) than the crops grown under CTS. The greater yield attributes under SRI were due to better growth, as crops under SRI were taller, had more tillers, and dry weight at different stages of crop growth. In both SRI and CTS, higher fertilizers resulted in better growth, yield, and yield attributes; moreover, the optimum fertilizer dose was 100% RDF.